A new series of 1,3,4-oxadiazole derivatives: Synthesis and evaluation of antimicrobial activity - TOK, FATİH (My University, 2021)
Aim: Infectious diseases have become more and more life-threatening illnesses. Despite a large number of antimicrobial agents, deaths due to infectious diseases are increasing day by day. Antimicrobial drugs have remained insufficiently against some infectious diseases caused outbreaks such as Zika, Ebola, SARS and MERS coronaviruses during the last decades. Therefore, new antimicrobial agents are urgently needed. 1,3,4-Oxadiazole ring is an important pharmacophoric group which is exhibited a broad spectrum of pharmacological activity profile including their antibacterial, antifungal, antiviral, antimalarial, antitubercular properties (1). In this study, we aimed the synthesis of new 1,3,4-oxadiazole rings and evaluation of their antimicrobial activity. Methods: New 2,5-disubstituted-1,3,4-oxadiazoles were synthesized at three steps. All compounds were characterized with spectral methods such as IR, 1H-NMR, 13C-NMR and elemental analysis. The antimicrobial activity of 1,3,4-oxadiazoles was screened on four bacteria and three fungi according to our previous method (2). Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus were used for antibacterial activity; Candida albicans, Candida parapsilosis and Candida glabrata were used for anticandidal activity. Results: Minimum inhibitory concentration (MIC) was determined for test compounds and for the reference standards chloramphenicol, ketoconazole. The compound carrying methoxy substituent on the para position of the aromatic ring exhibited the same antibacterial activity as chloramphenicol against E. faecalis with a MIC50 value of 62.50 µM/mL. Conclusions: According to the results, we demonstrated that some compounds exhibit antimicrobial activities against tested microorganisms. Therefore, the oxadiazole nucleus is promising for new drug candidates.
Keywords: Antibacterial; antifungal; 1; 3; 4-oxadiazole